Similarities and Differences in the Peripheral Actions of Thyroid Hormones and Their Metabolites - Louzada, Ruy A.; Carvalho, Denise P. (Frontiers in Endocrinology, 2018)
Thyroxine (T4) and 3,5,3’-triiodothyronine (T3) are secreted by the thyroid gland, while T3 is also generated from the peripheral metabolism of T4 by iodothyronine deiodinases types I and II. Several conditions like stress, diseases and physical exercise can promote changes in local TH metabolism, leading to different target tissue effects that depend on the presence of tissue-specific enzymatic activities. The newly discovered physiological and pharmacological actions of T4 and T3 metabolites, such as 3,5-diiodothyronine (3,5-T2) and 3-iodothyronamine (T1AM) are of great interest. A classical thyroid hormone effect is the ability of T3 to increase oxygen consumption in almost all cell types studied. Approximately 30 years ago, a seminal report has shown that 3,5-T2 increased oxygen consumption more rapidly than T3 in hepatocytes. Other studies demonstrated that exogenous 3,5-T2 administration was able to increase whole body energy expenditure in rodents and humans. In fact, 3,5-T2 treatment prevents diabetic nephropathy, hepatic steatosis induced by high fat diet, insulin resistance and weight gain during aging in Wistar male rats. The regulation of mitochondria is likely one of the most important actions of T3 and its metabolite 3,5-T2, which was able to restore the thermogenic program of brown adipose tissue in hypothyroid rats, just as T3 does, while T1AM administration induced rapid hypothermia. T3 increases heart rate and cardiac contractility, which are hallmark effects of hyperthyroidism involved in cardiac arrhythmia. These deleterious cardiac effects were not observed with the use of 3,5-T2 pharmacological doses, and in contrast T1AM was shown to promote a negative inotropic and chronotropic action at micromolar concentrations in isolated hearts. Furthermore, T1AM has a cardioprotective effect in a model of ischemic/reperfusion injury in isolated hearts, such as occurs with T3 administration. Despite the encouraging possible therapeutic use of TH metabolites, further studies are needed to better understand their peripheral effects, when compared to T3 itself, in order to establish their risk and benefit. On this basis, the main peripheral effects of thyroid hormones and their metabolites in tissues, such as heart, liver, skeletal muscle and brown adipose tissue are discussed herein.